Solar Still; Unrevealed Facts And Reasons Causing Its Low Productivity - Siti Nudra Shafinie, Abdul Aziz; Omar, El-Hadad; Syarifah, Abd Rahim; Chew, Few Ne (Kuwait University, 2017)
As the current techniques for water desalination are very costly because of the high demand of electrical power or fossil fue, desalination of seawater using solar energy is one of the ways to meet the growing water demand at low cost. With the technologies currently available, solar still fresh water production rate is very low, compared to other techniques. The low production rate has been the main reason behind the lack of industrial usage of solar stills. As the maximum temperature which can be reached within the solar still is not very high, the evaporation rate inside the solar still remains low. This low temperature is the main reason for such a massive disadvantage, resulting in reduced heat transfer rate and slow vaporization process. This research aims at analyzing the reason for solar still low productivity, and suggesting some design modifications to solve such a crucial problem. This is done by dividing the solar still evaporation into four processes, then every process is thoroughly analyzed to solve the main problem, and to provide the maximum temperature and heat transfer rate inside the solar still. With this problem solved, use of solar still in industry can become a possibility.